2017
DOI: 10.18632/oncotarget.15351
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology-based and clinically relevant prediction of the active ingredients and potential targets of Chinese herbs in metastatic breast cancer patients

Abstract: Chinese Herbal Medicine (CHM) plays a significant role in breast cancer treatment. We conduct the study to ascertain the relative molecular targets of effective Chinese herbs in treating stage IV breast cancer.Survival benefit of CHM was verified by Kaplan-Meier method and Cox regression analysis. A bivariate correlation analysis was used to find and establish the effect of herbs in complex CHM formulas. A network pharmacological approach was adopted to explore the potential mechanisms of CHM.Patients in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 69 publications
0
49
0
Order By: Relevance
“…In addition, the tumor-suppressive potential of plant bioactive molecules also includes intensively discussed targeting of the aberrant epigenetic modifications particularly on the level of the global DNA hypomethylation status of the cells, hypermethylation of tumor suppressor gene promoters, histone post-translational modifications, and non-coding RNA (ncRNA)-linked multi-gene network modulations [10][11][12][13]. However, regarding clinical research, only a relatively limited number of epidemiological studies and meta-analyses have documented that regular (4-5 times a week) and long-term (several years) consumption of selected whole plant foods (not isolated molecules) is significantly associated with a decrease in cancer risk, including breast carcinoma (BC) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the tumor-suppressive potential of plant bioactive molecules also includes intensively discussed targeting of the aberrant epigenetic modifications particularly on the level of the global DNA hypomethylation status of the cells, hypermethylation of tumor suppressor gene promoters, histone post-translational modifications, and non-coding RNA (ncRNA)-linked multi-gene network modulations [10][11][12][13]. However, regarding clinical research, only a relatively limited number of epidemiological studies and meta-analyses have documented that regular (4-5 times a week) and long-term (several years) consumption of selected whole plant foods (not isolated molecules) is significantly associated with a decrease in cancer risk, including breast carcinoma (BC) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, TCM served as important parts of complementary and alternative medicine to provide a theoretical and practical approach to the treatment of gastric cancer combined with other conventional cancer therapies. And TCM was confirmed that it could not only improve the clinical symptoms, immune functions and performance status of cancer patients, but also prolong their survival period [ 109 110 ]. Moreover, Kangai injection was made from ginseng, Astragalus, Sophora flavescens, and its functions were replenishing Qi and strengthening the body resistance owing to its active components, namely Astragalus saponins, ginsenoside, and matrine.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, TCMSP database was used to screen the compounds based on DL (drug-likeness) values. Only ingredients with a DL value higher than 0.18 can be retained as candidate compounds (Xiang et al, 2016 ; Mao et al, 2017 ). For the identification of GJE associated proteins and genes, STITCH (“search tool for interactions of chemicals”) database 4.0 ( http://stitch.embl.de/ ) was used to explore the compound-protein interactions of GJE.…”
Section: Methodsmentioning
confidence: 99%